Analisis Studi Kelayakan Bisnis Pada Pengembangan UMKM Usaha Tahu Dan Tempe Bapak Yulianto Ditinjau Dari Aspek Keuangan - Ramahdani, Dita; Handayani , Sri; Sachanovrissa , Silke (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the business feasibility of Pak Yulianto's tofu and tempeh business, and to determine the feasibility from a financial aspect. Meanwhile, the research method used for financial aspects uses the Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI) research methods. The results of this research show that the tofu and tempeh business is considered viable because the business location is strategic and easy to reach by consumers, the technology used is modern and the production process is easy. From the results of the financial aspect analysis, it shows that the tofu and tempe business is said to be feasible to run with a projected life of 5 years at a discount rate of 10%. Analysis of eligibility criteria for income payback period (PP), net present value (NPV) of IDR 114,505,137 , the profitability index (PI) value is 1.15% and the internal rate of return (IRR) is 23%.